Employers' Perspective on Successful Accounting Information System Internships: A Case Study in Pampanga, Philippines - Guanlao, Benedict M.; Calma, Patricia Ann; Jacinto, Janelle A.; Quilicol, Kimberly G.; Estacio, Regine C.; Orlanes, Aljiec M.; Yangga, Angelica Mae G.; Sonza, Andrea R.; Cuellar, Sugar Kate M.; Tua, Ronalyn R.; Calara, Heart MacKenzie N.; Miranda, John Paul P.; Mallari, Gienahlyn M. (Universitas Muhammadiyah Surakarta, 2023)
This qualitative case study aims to identify the essential skills required by employers when hiring AIS student interns. Additionally, it explores potential recommendations for the university to ensure a successful internship experience for AIS undergraduates. Ten employers were interviewed in person, including six from the accounting and banking industries and four from non-accounting or government sectors. Thematic analysis was employed to analyze the collected data. The study emphasizes the significance of employers' perspectives in helping students prepare for actual work in the industry and guiding the university in enhancing its program structure. The study identified both hard and soft skills necessary for student interns. Hard skills encompass technical proficiency and fundamental accounting knowledge, while soft skills encompass effective communication, teamwork ability, analytical aptitude, time management, adaptability, willingness to learn, trustworthiness, and discipline. Employers emphasize these skills when considering student interns. Furthermore, the study reveals employers' recommendations to the university, including conducting an initial assessment before deployment, ensuring well-trained interns, providing comprehensive support throughout the internship, fostering collaboration between the university and employers, and enabling students to focus on internships without additional subjects. These suggestions serve as valuable insights for the university to enhance the internship program not only for AIS undergraduates but also for students pursuing other professions. The findings of this research can be used as a foundation for future implementation of internship programs, aiming to facilitate successful internships for Accounting Information System undergraduates and students in various field.